Torsional behaviours and crack localization in palm oil clinker concrete / Safdar Khan - Safdar, Khan (2021)
The utilization of a Palm oil clinker for the production of sustainable lightweight concrete has environmental, economic, and social benefits. This study presents the investigation of the torsional behavior and localization of cracks in concrete at different substitution levels of POC coarse aggregate with granite. The DOE method was used for the design of the control mix, and all other mixes were prepared with the substitution of granite with the increasing amounts of POC at replacement levels of 20%, 40%, 60%, 80%, and 100%. The maximum reduction in the hard density, compression strength, splitting tensile strength, and flexural strength was 18.80%, 37.25%, 30.94%, and 15%, but an increment in water absorption of 1.78 times higher than the POC0 mix at the full substitution of POC with granite. The impact energies (first and failure cracks) at 60% and 100% incorporation of POC were approximately 4 and 1.60 times higher than control mix. The torque at initial and ultimate cracks were decreased by increasing the substitution levels of POC coarse aggregate. The POC100 had 1.64, and 2 times lower initial torsional stiffness, and torsional toughness as compared to NWC. The initial crack has happened almost in the range of 14-25% of the ultimate crack. The rise in the AE activities, when the initial, and ultimate cracks have developed accompanied by a dropped in the torque-twist curve, after the ultimate torque. The initial crack, ultimate crack, initial, and ultimate torque have been investigated by using the acoustic emission parameters such as absolute energy, and cumulative signal strength